2011
DOI: 10.1002/pssa.201000630
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic properties of nanostructured GdTb thin films

Abstract: Various series of Gd100−xTbx films and multilayers with a different thickness of rare earth (RE) layers were prepared by rf‐sputtering. The increase of Gd content leads to an increase of the magnetic ordering temperature (Tord). At the same time substitution of the low anisotropic gadolinium by high anisotropic terbium causes an increase of the coercivity of the samples. The decrease of the RE layer thickness (LRE) results in the change of the RE films structure: the crystalline grain size goes down and for LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…3,4 While the MCE is most frequently studied in bulk materials, there has been some effort recently to explore the MCE in nanoscale materials. [5][6][7][8][9][10][11][12] In Refs. 5 and 6 it was shown that finite size effects can detrimentally impact the magnetic entropy change in Gd/W multilayers.…”
mentioning
confidence: 99%
“…3,4 While the MCE is most frequently studied in bulk materials, there has been some effort recently to explore the MCE in nanoscale materials. [5][6][7][8][9][10][11][12] In Refs. 5 and 6 it was shown that finite size effects can detrimentally impact the magnetic entropy change in Gd/W multilayers.…”
mentioning
confidence: 99%
“…Thus, prerequisites for realization of the so-called table-like MCE in the same material appear. Additionally, it was found that both the epitaxial Gd films and Gd-based multilayers show a remarkable depression of T C following the finite-size scaling [6], [8]. Thus, Gd layer variation can tune T C , which establishes the optimal operating temperature.…”
Section: Introductionmentioning
confidence: 97%
“…Gd thin films and Gd-based multilayers are the subjects of study as model systems for MCE in nanostructured materials focused on possible applications for the refrigeration of electronic chips and other small dimension devices [5], [6]. Sputtering deposition of nanoscale Gd multilayers is a simple way to get gadolinium in a nanocrystalline state.…”
Section: Introductionmentioning
confidence: 99%
“…11 Other studies on Gd-based structures demonstrated that the MCE also depends on the size and dimension. 12,13 Indeed, it appears that the combination of interfaces, defects, and lower size can explain the enhancement of MCE for low dimension samples. For instance, a maximum of entropy was observed in Gd/W multilayer.…”
Section: Introductionmentioning
confidence: 99%